(untitled) (Scientific journal of the Fergana State University, 2026)
This study investigates the effects of incorporating locust meal as an alternative protein source into the diet of broiler chickens on their growth, physiological, and immunological parameters. The experimental groups were fed diets containing 15% and 25% of Dociostaurus maroccanus and Dericorys albidula meal, respectively. The findings revealed that locust meal inclusion significantly enhanced body weight gain, improved blood cell composition, and increased immunoglobulin (IgG, IgM) levels. Furthermore, elevated total protein, albumin, and globulin concentrations indicated improved protein metabolism. The results demonstrate that locust meal can serve as an effective, eco-friendly, and economically viable protein source for sustainable poultry production.